The disciplinary adjective regime within the framework of due process (2011)
There are serious failures, of rational, structural and material nature on the procedu ral disciplinary order in Colombia, which, far from being a manifestation of the Social. State of Law, stands as an inquisitorial system, arbitrary and subjective, in which the individual is instrumented, stripping it of its status as an "end in itself" (subject), and it becomes a procedural object, thus ignoring the essential of due process.